Developing Competency Assessment for Cook Helper: A Systematic Literature Review - Dyah Putri; Rina Febriana Hendrawan; Guspri Devi Artanti; Constantinus Rudy Prihantoro; Muhammad Nurtanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The global workforce’s rapid evolution and the complexities of Industry 4.0 necessitate a paradigm shift in Technical and Vocational Education and Training (TVET). Modern institutions are required to produce graduates who possess not only specialized practical skills but also robust non-technical competencies to navigate unpredictable professional environments. Despite the emphasis on workforce readiness, a significant research gap persists in contextualizing general TVET competencies into specific, actionable assessment frameworks for niche professions, such as the cook helper role in the culinary industry. This study aims to bridge this gap by conducting a qualitative Systematic Literature Review (SLR) of 30 peer-reviewed articles to identify core technical and non-technical competency variables. The findings reveal that while hard skills—such as culinary technique mastery, food safety, and hygiene—remain foundational, soft skills like adaptability, resilience, and effective communication are equally decisive for long-term career sustainability. This study successfully adapts these general TVET variables into specific, measurable indicators for cook helpers, emphasizing procedural precision and adherence to industry standards. Furthermore, the proposed assessment framework integrates work-based, interpersonal, and behavioral evaluations, offering a holistic measurement tool for SMK students. The study concludes that assessment frameworks in vocational education must transition from product-oriented testing to authentic, performance-based evaluations, particularly when implemented within Teaching Factory ecosystems.